Radix Intelligence: A new definition and integrative model of intelligence. (1st February 2021) - Petrides, Konstantinos V.
Abstract: This paper introduces Radix Intelligence, a new definition and integrative model of intelligence developed within the overarching system of Psychobionomy (Petrides, 2019). Following a discussion of misconceptions and pitfalls plaguing existing models of intelligence, with emphasis on the IQ literature, I point at Radix Intelligence as the primal energy underpinning mind activity in its entirety. All existence unfolds according to the laws of Radix Intelligence, whose nature is collective, impersonal, and non-local. Within the confines of the personalized human mind, the self-construct, a latent structure within the Thinking stage of the Psychobionomic system, refracts the unitary flow of Radix Intelligence into a manifold of major traits, including trait cognitive, trait emotional, and trait social intelligence, among others. In the context of elucidating Radix Intelligence, I offer a radical reinterpretation of the so-called "crud factor" and also touch on the issue of common method variance. Theoretical implications of Radix Intelligence are discussed with reference to the need for dynamic integration across the whole field of differential psychology, and practical implications with dual reference to the potential for establishing a new field of subconscious psychometrics and the pressing urgency for the individual to transition from a psychology of becoming to a psychology of being.